Unveiling Linguistic Awareness: A Narrative Inquiry Into A Teacher’s Experiences In EFL Classrooms - Setyaningsih, Bernadeta (CV. Inara, 2024)
Language is used in our daily interactions to fulfil many different goals such as communicating information, ideas, beliefs, emotions and attitudes to one another orally or writtenly. To ensure the language is perceived appropriately, language learners should know about a language, how it is learned, how it is used, in order to achieve some purpose or solve some problems in communication. Applied linguistics in language teaching will help learners to deal with solving or at least ameliorating social or communicative problems involving language. This study aimed to explore the awareness of incorporating linguistics knowledge in EFL classrooms. The central issues of this study are challenges and strategies employed by the teacher to deal linguistics errors which appeared upon teaching listening in the classroom The study applied a narrative inquiry. The findings revealed that linguistics knowledge incorporated by teachers during the classroom learning were desperately needed to help students in understanding the tasks given and to facilitate students in communicating their ideas orally or writtenly.